Di-Higgs production via axion-like particles - Esser, Fabian; Madigan, Maeve; Salas-Bernárdez, Alexandre; Sanz, Veronica; Ubiali, Maria (Journal of high energy physics, 2024)
Due to the pseudo-scalar nature of the axion-like particle (ALP), the CP-conserving production of two Higgs bosons via the ALP necessarily involves an additional Z or γ boson. We examine the existing constraints from di-Higgs searches at Run 2 of the LHC and find that, despite the presence of extra objects in the final state, these searches are sensitive to a combination of ALP couplings to gluons and three-bosons in the TeV scale range. Additionally, we propose a specialized search strategy incorporating an energetic leptonic Z boson. This refined ALP-induced production process would allow for the identification of the h h → 4 b-jet final state and could potentially probe the TeV scale using data from Run 2 of the LHC. This production process can also occur through a coupling between the top quark and the ALP. We translate the current constraints on di-Higgs production into new limits on the ALP-top coupling.
Gesehen am 30.04.2025